Pelatihan Penerapan Teknologi Mesin Cerdas Sterilisasi Media Jamur Tiram Bagi Anggota Kelompok Petani Jamur Tiram Tegal: Training on the Application of Smart Machine Technology for Sterilizing Oyster Mushroom Media for Members of the Tegal Oyster Mushroom Farmers Group - Sukur, Muji; Utomo, Mardi Siswo; Sari, Anisa Rachma; Ningsih, Dewi Handayani Untari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Microbial contamination in making oyster mushroom planting media is a problem that every mushroom farmer often experiences. The main obstacle experienced by farmers is that the level of contamination in making media is still high, around 20%. This causes mushroom farmers to be reluctant to make their mushroom media (baglog). The application of intelligent machines to control the sterilization process of mushroom media controlled by a microcontroller is expected to overcome the problems experienced by farmers. The training program for making oyster mushroom media is a significant effort to support the growth and development of the oyster mushroom cultivation industry. This abstract summarizes the training program's objectives, methodology, results, and impact in increasing farmers' understanding and skills in producing high-quality media for oyster mushroom cultivation. This program aims to provide in-depth knowledge to participants, starting from mixing the composition of ingredients, the sterilization process, and the process of planting seeds (inoculation) in accordance with media-making standards. Through intensive training, participants learn the latest raw material selection, formulation, sterilization, and media packaging techniques. The training also includes hands-on media-making practice, enabling participants to master the necessary skills. In addition, this training program also allows participants to understand the importance of sustainable practices in oyster mushroom cultivation by integrating ecological aspects in media production. This helps in maintaining environmental balance and supports sustainable industrial growth.